Uropathogenic Еscherichia coli strains: biological properties and colonization activity - Kuznetsova, M.V.; Gizatullina, J.S.; Demakov, V.A. (Perm Federal Research Centre Journal, 2019)
The problem of catheter-associated urinary tract infections is caused by the active colonization of embedded medical materials by bacteria and biofilm formation. The article presents the characteristics of urinary and catheter-associated nosocomial Escherichia coli (UPEC) strains. It observes biofilm formation and UPEC viability on different types of urological catheters both in monoculture, and associations in vitro . The influence of the properties of the attacked surface, as well as environmental factors, on the colonization activity of bacteria has been shown in the study.